PEMANFAATAN MEDIA VIDEO POROS MARITIM UNTUK MENINGKATKAN PEMAHAMAN SISWA PADA MATA PELAJARAN GEOGRAFI KELAS XI DI SMA NEGERI 1 TALANG KELAPA (Universitas Negeri Semarang, 2019)
Problem formulation in this research is whether the use of maritime axis video media can improve students' understanding of class XI geography in SMA Negeri 1 Talang Kelapa. This study aims to determine the use of maritime axis video media to improve students' understanding of class XI geography subjects at SMA Negeri 1 Talang Kelapa. The research method used in this research is quantitative experiment with data collection techniques obtained using tests and documentation. The average value of student learning outcomes in the experimental class can be categorized well that is 80.17 using maritime axis video media, while the average value of control class learning outcomes by not using maritime axis video media can be categorized sufficiently with the average student learning outcomes is 61.94. Based on the calculation, obtained t count> t table = 8,400> 1,667 that is t count = 8,400 and t table = 1,667, then accept the hypothesis (ha) which means